Inward Foreign Direct Investments (FDI) and Location Choice Determinants: Empirical Evidence from India - Sixtus Cyprian Onyekwere; Oludamilola Otuyelu (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
The main purpose of this research was to determine the nature of the relationship between inward FDI flow into India and selected sets of FDI location determinants. The paper also investigates the exact impact of the individual FDI location determinants on inward FDI flow into India. Following these objectives, eight variables relating to the inward FDI locational advantage theory were selected, with data running from 1965-2018. The investigated location determinants for inward FDI include tax, market size (GDP), a measure of market potential (GDPPC), human capital (education), wage cost, Ease of Doing Business (DB), and measure of economic progress (GDP growth). The method of data analysis involved the application of OLS regression, taking note of the necessary assumptions for the use of OLS. The results of the study indicate that GDP growth is the only significant FDI location determinant in India, with a positive impact of about 0.57. This implies that the Indian government should prioritise policies that seek to boost GDP